Three-Dimensional Motion Analysis of Lip Movement in Patients with Mandibular Prognathism - MATSUBARA, TAIKI; MORISHIMA, SHIGEO; SAITO, ISAO; NAKAMURA, YASUO; HAYASHI, TOYOHIKO; TERADA, KAZUTO (The Japanese Journal of Jaw Deformities, 2007)
Aim: The purpose of this study was to introduce our newly developed three-dimensional system of analyzing the lip movement synchronized with mandibular movement and to analyze the relationships between lip movement and mandibular movement before and after orthognathic surgery in skeletal Class III patients using this system. Materials and Methods: The subjects comprised 8 skeletal Class III patients who had undergone bilateral sagittal splitting mandibular ramus osteotomy and 8 persons with individual normal occlusion. Materials consisted of three-dimensional movement values obtained by a motion capture system equipped with two infrared CCD cameras, and three-dimensional static values measured by the three-dimensional optical laser scanner. Four landmarks affixed on the soft tissue around the mouth and four other landmarks to estimate the lower incisor movement were measured for 30 seconds during habitual mouth opening and closing movement. The relationships between lip movement and the lower incisor movement were compared between the pre-and post-operation and the normal groups. Results: The system developed in this study enabled three-dimensional measurement of lip and lower incisor movements during habitual mouth opening and closing at the same time. The landmarks on the lower lip, the right and left angles of the mouth and the chin point moved further in the pre-operation group than those in the post-operation and normal groups during habitual mouth opening and closing. Three-dimensional movement values after surgery showed a tendency to be close to those in the normal group. Conclusion: The present system may be useful for accurately measuring the movement of the lip synchronized with the lower incisor movement. Post-operative smooth movement of the soft tissue around the mouth suggests that tension of the muscles between the hard and soft tissues observed before surgery might decrease after surgery.